PENGELOLAAN PELATIHAN OLAHRAGA PENCAK SILAT UNGGUL DI PPLP PENCAK SILAT JAWA TENGAH - TARMIN , TARMIN (2011)
The aims of this research are : (1) describing the characteristics of training plan of Pencak Silat in PPLP Pencak Silat Jawa Tengah, (2) describing the characteristics of training process of Pencak Silat in PPLP Pencak Silat Jawa Tengah, (3) describing the characteristics of training evaluation of Pencak Silat in PPLP Pencak Silat Jawa Tengah. The research used a qualitative descriptive research. The methods used to collect the data are observation, interview and documentation. The data sources of the research are the athletes, trainers, co-trainers, and the chairmen of PPLP Pencak Silat Jawa Tengah. The data are validated with data triangulation. While the result of this research are: 1) the training plan in PPLP Pencak Silat Jawa Tengah is done to fulfill the quality of training standard, 2) the training process is in four variables namely; trainers, students, training process and product in the form of the students' ability improvement. The trainers have to be able to manage the four variables so that the process can run well. 3) Evaluation has an important role in training process. The evaluation is done in the form of physical test and technical ability test. Physical test includes strengths, endurance, ability, and power.